Constructing the interface: Crossings between the public and the private - Goldman, Amy-Leigh (Faculty of Engineering and the Built Environment, 2023)
The built fabric of the city of Cape Town reflects the social and economic inequalities within its citizenship. Contemporary practices of inner-city living tend to cater to the wealthy while social housing on the periphery continues to exclude the poor from basic services and access to opportunities. Salt River is one of the areas identified by the city, for the provision of inner-city affordable housing. The area is prone to spatial acts of violence that lead to a loss of culture and heritage through gentrification and displacement. This project aims to re-think the density of housing precincts as not only spaces of residence but also spaces that facilitate better socio-spatial experiences for its residents that may assist in the prevention of the deterioration and destruction of existing neighbourhoods. The research aims to seek methods that explore crossing the boundary between public and private while challenging the relationship between the two, creating a more accessible city. By looking at the construction of the interface the project aims to create a space where the everyday social practices of the private extend into the public, shaping safer more socially interactive neighbourhoods that continue to develop shared cultural practices. The project locates itself on the Salt River Market site, one of the proposed sites earmarked for affordable housing by the city. The Dissertation explores an inner-city housing project that focuses on reimagining the public life of the market and unifying it with housing across the parcel of land. The design focus is on a transitional housing block that provides a space for residents to temporarily stay as they move from current living conditions on the market to the new proposed housing. Through the process of design, the project presents opportunities for better integrating affordable housing into the public life of the city.